Prevalence of Anxiety and Depression among Patients Attending Outpatient Clinics in Hawler Teaching Hospital - Hamad, Abdulqader Hussein; Ramazan, Sawza Hameed; Farag, Taha Ahmad (Sulaimani Journal for Pure and Applied Sciences, 2013)
Background and objectives: The present study was designed to determine the prevalence of anxiety and depression among the client who visit the outpatient (medical surgical and dermatology) unit. Methods: A descriptive study was carried out by investigators from (November 2011 to February 2012) in (medical, surgical & dermatology) outpatient units In Hawler Teaching Hospital. Results: The results found that (62.3%) of patients have anxiety, among them 28.4% have mild anxiety (28.4%) have moderate anxiety and10.6% have severe anxiety, the results also found that 50% of patients were suffering from depression, among them 25.4% were mild, 19.9%were moderate and 4.7% were severe. The overall prevalence of psychological disorder is more in early stage of life & more common in male, no educated and married people. Conclusion: the study concluded that the prevalence of anxiety and depression among the client visiting outpatient in Hawler Teaching Hospital is appeared great anxiety and depression that have a significant burden on the society, which the client don’t visit psychiatrist, So increased public and professional awareness of psychological care might decrease the size of outpatient clients.